Hope Speech Detection Using Social Media Discourse (Posi-Vox-2024): A Transfer Learning Approach - Muhammad Ahmad; Usman Sardar; Farid Humaira; Ameer Iqra; Muhammad Muzzamil; Ameer Hmaza; Grigori Sidorov; Ildar Batyrshin (Journal of Language and Education)
Background: The notion of hope is characterized as an optimistic expectation or anticipation of favorable outcomes. In the age of extensive social media usage, research has primarily focused on monolingual techniques, and the Urdu and Arabic languages have not been addressed.